Recent Progress on Feasible Strategies for Arbutin Production - Xu, Ke-Xin; Xue, Meng-Ge; Li, Zhimin; Ye, Bang-Ce; Zhang, Bin (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Arbutin is a hydroquinone glucoside and a natural product present in various plants. Arbutin potently inhibits melanin formation. This property has been exploited in whitening cosmetics and pharmaceuticals. Arbutin production relies mainly on chemical synthesis. The multi-step and complicated process can compromise product purity. With the increasing awareness of sustainable development, the current research direction prioritizes environment-friendly, biobased arbutin production. In this review, current strategies for arbutin production are critically reviewed, with a focus on plant extraction, chemical synthesis, biotransformation, and microbial fermentation. Furthermore, the bottlenecks and perspectives for future direction on arbutin biosynthesis are discussed.